Photochemical Reactions of Benzene with Chlorine Radicals in Atmospheric Aqueous Phase - Linchang Dong; Yu Lei; Jun Lu; Han He; Yue Yang; Chengzhu Zhu (Journal of Chemistry)
The chlorine radicals (Cl• and Cl2•−) have profound impacts on the photochemical processes in the atmospheric aqueous phase (e.g., marine clouds). However, current literature lacks information on the Cl•/Cl2•−-induced transformation of organics under sunlit irradiation. In this work, the reaction mechanism of chlorine radicals with benzene (a representative VOC) in the atmospheric aqueous phase was investigated by using 355 nm laser flash photolysis, 365 nm UV light steady state, and real sunlight experiment. The results showed that Cl•/Cl2•−-initiated reactions were crucial steps for the consumption and transformation of C6H6, where the conversion rate of benzene decreases with the increase of pH and initial species concentration. Cl• attacked benzene ring to produce the Cl-CHD (6-chlorocyclohexadienyl radical) with a second-order rate constant of (1.2 ± 0.3) × 1010 M−1·s−1, while the rate constant for Cl2•− was much lower ((4.5 ± 0.3) × 106 M−1·s−1). The addition of Cl• and Cl2•− to benzene generated chlorobenzene and dichlorobenzene and ring-opening substances during the further oxidation reaction, which had been also demonstrated in the real sunlit experiments. This work provides fundamental kinetic and mechanistic insights into benzene’s photochemical transformation by Cl•/Cl2•−, facilitating the understanding of VOC transformation in atmospheric waters.